Punctuated Equilibrium Policy of Village Government Budget Following the Pandemic - Israwan Setyoko, Paulus; Kurniasih, Denok; Satwika Wijaya, Shadu (KnE Social Sciences, 2023)
The pandemic has resulted in changes to public policy, particularly in public budgeting. This is the case not only at the central level but also at local and village government levels. The challenge of changing public policy also occurs in the fiscal policy sector. Village governments are required to reallocate their budgets for activities to handle the pandemic and post-pandemic economic recovery. Hence, this article aims to describe changes in village government budgeting policy changes from the perspective of punctuated equilibrium in public policy studies. The data in this study were obtained through focus group discussions and secondary data collection. The study found that the political equilibrium of a policy cannot last forever. Policy changes occur if there is a change in the agreement between policy-making actors. Public policy changes have so far been understood to occur slowly and gradually. However, this article proves that it can occur drastically and within a short period of time. Keywords: fiscal decentralization, local autonomy, policy change, public finance, punctuated equilibrium public policy, rural local government budget